(3GdefJNH ef GdSjGb dJGQjN fjSCHhQs - (3EHQGgje Hf eMeO Hf GdCRgQ GdUQjajfis; (3CHj GdMSf YHO GdZGaQ Hf ESeGYjd Hf YHO GdZGaQ GdaGQSjs
(3ChdgG (B:s
(3CeG HYO abO TGQ Ydi HYV GdCYRI ef GdENhGf Cf CbUO Edi LeY cJGH jTJed Ydi PcQ GdeTGjN ef YdeGA fjSGHhQ s
(3BNQgG (B:s
(3BNQ GdefJNH aQY efgG SfI (B622 (3g` s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3GNJjGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B623 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B299 s
Keywords: (3GdJGQjNs